Effect of hip abduction maximal voluntary isometric contraction on lumbar motion and power output during the back squat - Kelly, C. F.; Gonzalez, A. M.; Spitz, R. W.; Sell, K. M.; Ghigiarelli, J. J. (International Journal of Kinesiology & Sports Science, 2018)
Background: Post-activation potentiation (PAP) is a neuromuscular phenomenon that has been shown to augment muscular force generating attributes as well as neural and sensory recruitment. While PAP has demonstrated to acutely enhance muscular performance during high-intensity activities, the effect of PAP on lumbopelvic kinematics under load remains unknown. Objectives: The purpose of this study was to examine the potential PAP effect of a hip abduction maximal voluntary isometric contraction (MVIC) on lumbar motion and power output during the barbell back squat. Methods: Nine resistance-trained men (22.9±2.3 y; 85.0±13.8 kg; 174.3±5.1 cm) performed a set of 5 repetitions of the barbell back squat using 80% one-repetition maximum with and without a hip abduction MVIC prior to performance. Experimental and control trials were randomized and counterbalanced among participants. MVIC was carried out via manual long-lever hip abduction. During the back squat exercise, lumbar motion analysis was performed using wireless motion-sensor technology, and power output was assessed via an accelerometer. Results: No significant differences were observed between trials for lumbar flexion range of motion (ROM) (p=0.32), lumbar flexion maximum deviation (p=0.32), lumbar lateral flexion ROM (p=0.81), lumbar lateral flexion maximum deviation (p=0.98), lumbar rotation maximum deviation (p=0.70), average peak power (p=0.98), or average mean power output (p=0.99) during the squat protocol. Conclusions: Implementation of a manual long-lever hip abduction MVIC prior to the back squat exercise did not significantly alter lumbar motion or augment power output in resistance trained males.